Tiger daughter - Lim, Rebecca (Australia : Allen&Unwin, 2021)
"Wen Zhou is a first-generation daughter of Chinese migrant parents. She has high expectations from her parents to succeed in school, especially her father, whose strict rules leave her feeling trapped. She dreams of creating a future for herself more satisfying than the one her parents expect her to lead. Then she befriends a boy named Henry who is also a first generation immigrant. He is the smartest boy at school despite struggling with his English and understands her in a way nobody has lately. Both of them dream of escaping and together they come up with a plan to take an entrance exam for a selective school far from home. But when tragedy strikes, it will take all of Wen's resilience and tiger strength to get herself and Henry through the storm that follows"--Provided by publisher.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, August 2023
Kirkus Starred, June 2023
Pub Weekly, July 2023
Keywords: Children of immigrants -- Juvenile fiction; Chinese -- Australia -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Friendship -- Juvenile fiction; Immigrants -- Juvenile fiction; Children of immigrants -- Fiction; Chinese -- Fiction; Coming of age -- Fiction; Family problems -- Fiction; Friendship -- Fiction; Immigrants -- Fiction; Children of immigrants -- Fiction; Chinese -- Australia -- Fiction; Family life -- Fiction; Friendship -- Fiction; Immigrants -- Fiction; Australia -- Fiction; Bildungsromans